Age related variations in the morphometric parameters of the mitral valve complex- A cadaveric based study from Kolkata - Chunder, Rajasri; Majumdar, Sayantani; Dey, Arijit (Asian Journal of Medical Sciences, 2019)
Background: Mitral valve diseases are quite common in Indian Population across the age groups and the latest trend in the valvular surgery for better outcome is “Respect rather than Resect”. So, reconstructive surgeries being a preferred modality of treatment in Mitral Valvular Disorders, morphometric parameters of mitral valve are of immense importance. Aims and Objective: This study deals with the age wise variation of the morphometric parameters of the mitral valve. Material and Method: In this study, fifty formalin hardened cadaveric hearts were studied which were dissected and measurements of the morphometric parameters were recorded and analysed. Results: While analyzing the data on the weight of the heart,mean annular circumference (MAC), antero-posterior (APD) and transverse diameter (TD) of the mitral valve annulus, it was observed that all the parameters significantly increases with age. Conclusion: This data will be immensely helpful in planning the reconstructive surgeries of mitral valve age-wise.